Values Education from Perspectives of Classroom Teachers - Duban, Nil; Bülent Aydoğdu (European Journal of Social Science Education and Research, 2017)
Values education is a process, which begins at home and continues in society and in formal education institutions. The purpose of this research is to determine the opinions of primary school teachers about values education in primary schools. In the current research, the qualitative research method and focus group interview technique were used. The participants of the study were eight classroom teachers who were pursuing master’s degree at the classroom education program of Afyon Kocatepe University. The participants were selected using the intense case sampling, which is part of purposeful sampling technique. The data were collected through audio-taped group interview. The credibility of this study was enhanced by expert review. The interview schedule was sent to experts for review. The trustworthiness of this study was established by the formula proposed by Miles and Huberman. It was calculated as 0.92. The data collected from the interview were examined using a qualitative data analysis approach. The findings of the study showed that if value education starts at early ages it would provide much more opportunity to prepare for future life, to improve personality and to have long-lasting values. The participants argued that parents are very significant in value education. The participants suggested that value education should be either an independent course or certain values should be taught in existing courses. They also proposed that in value education case studies and drama can be used and that positive and desired behaviours and empathy should be encouraged among children.